The gospel of Luke - Gadenz, Pablo T. 1967- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2018)
"This Catholic commentary on Luke interprets Scripture from within the living tradition of the Church for pastoral ministers, lay readers, and students"--
Includes bibliographical references (pages 405-406) and indexes.
Keywords: Catholic Church -- Doctrines; Bible. -- Commentaries; Commentaries